COMPARISON OF ANTIBACTERIAL ACTIVITIES LEAVES EXTRACTS OF CERBERA MANGHAS AND LEAVES EXTRACTS OF AZADIRACHTA INDICA AGAINST KLEBSIELLA PNEUMONIAE - Musdja, Muhammad Yanis; Aeni, Markhamatul; Djajanegara, Ira (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aims to determine the potential of neem (Azadirachta indica, Juss) leaves and sea mango (Cerbera manghas, Linn.) leaves against Klebsiella pneumonia. Methods: Hexane and methanol extracts of neem leaves (A. indica, Juss) and hexane and butanol extracts of sea mango leaves (C. manghas, Linn.) were tested antibacterial against K. pneumonia using paper disc and dilution methods, measured the inhibition zone diameter, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC), as a comparison used ampicillin. Results: The MIC values for the butanol extract and hexane extract of sea mango leaves against K. pneumoniae were 1.124276 and 1.45958 mg/mL, respectively. While the MBC value of both of them had the same value, i.e. 2 mg/ml. The hexane and methanol extracts of neem leaves did not have potentially against the growth of K. pneumonia. Conclusion: Based on the results of this study have been obtained, that extracts butanol and hexane extract of leaves of sea mango (C. manghas, Linn.) have antibacterial activity strong enough against K. pneumonia, where, extracts butanol leaves of sea mango has antibacterial activity that is more powerful than the extract hexane leaf sea mango, while the methanol extract and hexane extracts of neem (A. indica, Juss) leaves have weak activity against K. pneumonia.